Spatio-temporal variation in wave power and implications for electricity supply. (December 2017) - Fairley, I.; Smith, H.C.M.; Robertson, B.; Abusara, M.; Masters, I.
Abstract: Wave energy resources are intermittent and variable over both spatial and temporal scales. This is of concern when considering the supply of power to the electricity grid. This paper investigates whether deploying arrays of devices across multiple spatially separated sites can reduce intermittency of supply and step changes in generated power, thereby smoothing the contribution of wave energy to power supply. The primary focus is on the southwest UK; SWAN wave model hindcast data are analysed to assess the correlation of the resource across multiple sites and the variability of power levels with wave directionality. Power matrices are used to calculate step changes in the generated power with increasing numbers of sites. This is extended to national and European scales using ECMWF hindcast data to analyse the impacts of generating power at multiple sites over wider areas. Results show that at all scales the step change in generated power and the percentage of time with zero generation decreases with increasing numbers of sites before plateauing. This has positive implications for performance of electricity grids with high levels of renewable penetration. Highlights: Wave energy resource has irregular intermittency causing grid integration concerns. Wave resource shows significant variability even between sites in close geographical proximity. Developing multiple sites across a region reduces step changes in power and time of zero generation. Results highlight the potential benefit to grid integration through selection of multiple sites.